All by myself, alone [compact disc, unabridged] : a novel - Clark, Mary Higgins (Clark, Mary Higgins. Alvirah and Willy., 2017)
Escaping the humiliation of her ex-fiancé's arrest, gems expert Celia Kolbride befriends Lady Emily Haywood, who is found dead at the hands of someone who has stolen the victim's emerald necklace.